A NiFeCu alloy anode catalyst for direct-methane solid oxide fuel cells - Wang, W.; Zhu, H.; Yang, G.; Park, H.; Jung, D.; Kwak, C.; Shao, Zongping (2014)
In this study, a new anode catalyst based on a NiFeCu alloy is investigated for use in direct-methane solid oxide fuel cells (SOFCs). The influence of the conductive copper introduced into the anode catalyst layer on the performance of the SOFCs is systematically studied. The catalytic activity for partial oxidation of methane and coking resistance tests are proposed with various anode catalyst layer materials prepared using different methods, including glycine nitrate process (GNP), physical mixing (PM) and impregnation (IMP). The surface conductivity tests indicate that the conductivities of the NiFe-ZrO 2/Cu (PM) and NiFe-ZrO2/Cu (IMP) catalysts are considerably greater than that of NiFe-ZrO2/Cu (GNP), which is consistent with the SEM results. Among the three preparation methods, the cell containing the NiFe-ZrO2/Cu (IMP) catalyst layer performs best on CH4-O2 fuel, especially under reduced temperatures, because the coking resistance should be considered in real fuel cell conditions. The cell containing the NiFe-ZrO2/Cu (IMP) catalyst layer also delivers an excellent operational stability using CH4-O2 fuel for 100 h without any signs of decay. In summary, this work provides new alternative anode catalytic materials to accelerate the commercialization of SOFC technology. © 2014 Elsevier B.V. All rights reserved.